Chat: ¿ "conversación escrita" o "texto escrito oralizado"? - Lisowska, Monika (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2006)
The aim of this paper is to show the discursive duality of the online conversation, also known as online chat. Although this kind of communication seems to be similar to face-to-face chat, it cannot be ignored that chatroom discourse is text-based. The author describes the online chat as a mixture of features from spoken and written discourse, wanting to answer whether it is closer to the one or to the other kind of discourse.
Chat: "written conversation" or "oral written text"?